Impact Of Christian Religious Education For Student School Intermediate First Background Behind Genre Trust Marapu In The District Rindi - Umbu Tunggul Tikawanda (FKIP, Universitas Palangka Raya, 2023)
Destination writing article this is for give description and explanation about impact of Christian Religious Education for student School Wow First in the District Rindi - East Sumba . this _ remember the existence of ancestral religions and local beliefs that still exist exist however children background behind Genre trust Marapu adhere one of the 6 legal religions in Indonesia which is recognized by the Ministry of Religion . Besides that writing this also explains about impact what just generated from exists behavior discriminatory to ancestral religions and beliefs local . Method research used is approach qualitative with use studies bibliography for collect data as ingredient writing article this . On the article this writer give the analysis about impact of Christian Religious Education for student School Intermediate first where the impact of Christian Religious Education gives influence to family and society generally .